Efficiency measurement of 1-D connected array using the Improved Wheeler Cap method - Sutinjo, Adrian; Belostotski, L.; Johnston, R.; Okoniewski, M. (2012)
We present a method for measuring antenna efficiency of a one-dimensional (1-D) connected array. The method is a modified version of the Improved Wheeler Cap method where the antenna under test (AUT) is electrically connected to two walls of the Wheeler Cap thereby simulating the 1-D array connection. Theoretical analysis based on cylindrical wave functions and numerical simulations with Method-of-Moments (FEKO) are presented to establish accuracy estimates for the method. Finally, we discuss measurement apparatus for measuring efficiency of a connected patch array.